O uso de grafos como motivação para o estudo de matrizes - Cáceres, Francisco Rafael (2021)
In high school the study of matrices has been mostly treated in a non-specific way. This work aim to present a proposition for teaching matrices using graphs. First the concept of graph, nomenclatures and types were defined. Then a short review of matrices was presented, including their operations and properties. Next, some applications of graphs were shown, as the emergence center and the Dijikstra’s algorithm, a problem situation modeled with graphs and solved with matrices. Finally, activities for the high school were indicated to teach matrices in a more effective and pleasurable way, relatated to the student’s life, to help teachers and students in the teaching and learning process.